Amphipod crustaceans (Corophiidea and Gammaridea) associated with holdfasts of Macrocystis pyrifera from the Beagle Channel (Argentina) and additional records from the Southwestern Atlantic - Alonso, Gloria Maria (2012)
Amphipod species inhabiting Macrocystis pyrifera holdfasts from the Beagle Channel were studied. The material was obtained by cutting plants at a depth of 8-12 m. Thirty-six corophiidean and gammaridean species were identified. Seven species were new and fourteen had been found previously in the Argentine Sea, although they enlarge their hitherto known geographical distributions along the littoral. Six species are new records from Uruguay. Full descriptions and figures are provided for the seven new species. In addition, new catalogue numbers are provided for those species formerly published without a formal deposit registration. The present work constitutes a paradigm in literature of the first comprehensive study of the amphipod fauna living in the holdfasts of Macrocystis pyrifera, a common and abundant plant in the kelp forests of the Beagle Channel. Moreover, distributional notes of the present list of the species are compared with similar data from the Southern Ocean.